Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.15288/jsad.2012.73.731
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Context and Intimate Partner Violence: Evidence From the California Community Health Study of Couples

Abstract: ABSTRACT. Objective: Couples in which one or both partners is a heavy or problem drinker are at elevated risk for intimate partner violence (IPV), yet little is known about the extent to which each partner's drinking in different contexts (volume consumed per setting in bars, parties, at home, or in public places) increases the likelihood that partner aggression will occur. This study examined associations between the volume consumed in different settings by each partner and the occurrence and frequency of IPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 40 publications
0
29
1
Order By: Relevance
“…Together these findings suggest a potential stress-response feedback loop, where the response (i.e., heavy episodic drinking) to a stressor (i.e., sexual assault) can increase exposure to subsequent stressors. Though we could not determine directionality of these findings, previous studies showed both that victimization can induce drinking (Begle et al, 2011; Keyes et al, 2011; Tyler et al, 2012) and that drinking environments can foster aggressive behaviors (Abbey, 2002; Cunradi et al, 2012; Mair et al, 2013; Studer et al, 2014), which may contribute to the sexual assault of transgender-identified people.…”
Section: Discussionmentioning
confidence: 68%
“…Together these findings suggest a potential stress-response feedback loop, where the response (i.e., heavy episodic drinking) to a stressor (i.e., sexual assault) can increase exposure to subsequent stressors. Though we could not determine directionality of these findings, previous studies showed both that victimization can induce drinking (Begle et al, 2011; Keyes et al, 2011; Tyler et al, 2012) and that drinking environments can foster aggressive behaviors (Abbey, 2002; Cunradi et al, 2012; Mair et al, 2013; Studer et al, 2014), which may contribute to the sexual assault of transgender-identified people.…”
Section: Discussionmentioning
confidence: 68%
“…There may be context-specific reasons for (and consequences of) heavy drinking (Cunradi et al, 2012; Jones-Webb et al, 2013; Levitt and Cooper, 2010; Mair et al, 2013; Neighbors et al, 2006; Zamboanga and Ham, 2008)—but no studies to our knowledge have investigated how these may differ by sexual orientation. Considering minority stress theory (Meyer, 2003) within a contextual perspective, we can see that some minority stressors (e.g., internalized homophobia/biphobia) and related processes (e.g., expectations of rejection, social norms) may be more prevalent and potent in certain settings, thereby influencing alcohol use within certain contexts for LGB populations.…”
Section: Discussionmentioning
confidence: 99%
“…We know even less about whether LGB and heterosexual students drink in similar or different contexts (e.g., bars, Greek parties, off-campus parties). Drinking locations matter because they can influence the amounts of alcohol consumed (Clapp et al, 2000; Paschall and Saltz, 2007) and risks of certain alcohol-related problems (e.g., intimate partner violence; Cunradi et al, 2012; Mair et al, 2013; Studer et al, 2014). Drinking contexts also have implications for how targeted prevention programs are designed, implemented, and evaluated (Wechsler and Nelson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, given that IPV is much more likely to occur in the home than in other locations [80], one might expect a stronger link with drinking in the home and therefore IPV would be more strongly associated with off-premises sales. On the other hand, to the extent that IPV is associated with heavier consumption [78, 81] and heavier consumption is more likely to occur in licensed premises, [8284] a stronger association might be expected for on-premise drinking. Further, whether the link is with on or off-premise drinking may vary by culture.…”
Section: Discussionmentioning
confidence: 99%